Gambaran Incidence Rate (HAIs) Berdasarkan Data Surveilans RSUP H. Adam Malik Periode Januari-Juni 2025 - Nurhayati, Nurhayati; Khairunnisa, Khairunnisa; Efri, Puti Miratil Hayati; Sinaga, Asmarani (Yayasan Jompa Research and Development, 2025)
This study aims to describe the Incidence Rate (IR) of Healthcare Associated Infections (HAIs) at H. Adam Malik General Hospital. The results are based on surveillance data obtained from the recapitulation of reports from the Infection Prevention and Control Committee for the period January–June 2025. The design used was quantitative descriptive with a retrospective study approach. The study population included all patients who used invasive devices (ventilators, urinary catheters, and central venous catheters) at H. Adam Malik General Hospital during the period of January–June 2025. Data analysis was performed descriptively from the results of the data and information obtained, then the percentages were presented in graph form. The results showed that the incidence of HAIs tended to decline throughout the first semester of 2025. The incidence rate of Central Line Associated Blood Infections (CLABSI) peaked in February (1.87‰), while ISK (Urinary Tract Infection) fluctuated, peaking at 0.67‰ in April and falling to 0‰ in June. Surgical site infections (SSIs) showed a spike in March (2.95‰) but gradually declined, with no cases at the end of the period. Meanwhile, ventilator-associated pneumonia (VAP) increased at the end of the semester to 0.99‰ in June. Infection control prevention efforts in hospitals are going well, but improved monitoring, regular training, and management support are still needed to maintain and strengthen the downward trend in HAIs.